Marrying Outside Your Tradition: A Practical and Spiritual Guide - Schaper, Donna (Rowman & Littlefield Publishers, 2023)
As membership in traditional churches or religious institutions plummets, the meaning of marriage is changing rapidly. Interfaith marriages are on the rise, creating new challenges from wedding planning to childraising. People of faith are marrying nonreligious people. Many question the institution of marriage itself. At a time when those identifying as spiritual but not religious is on the rise, Pastor Donna Schaper provides a roadmap to help readers to understand this continuing transition of marriage after both culture and religion are no longer of one voice about its meaning.